Dampak Sosial Media sebagai Sarana Teknologi Informasi di Lembaga pendidikan (Kajian Teoritis Perspektif Media Dependency Theory) - Rahmadi Bagus Wijaya; Muhamad Jamaludin; Zaenal Arifin (Advances In Education Journal, 2025)
This study aims to examine the impact of social media as a means of information technology in educational institutions, using Media Dependency Theory as a theoretical basis. This research explains how changes in communication, culture and social values in schools are affected by the use of social media. In addition, this study also highlights how dependence on social media can affect decision-making in educational institutions, both in managerial aspects and interpersonal relationships. Through a descriptive qualitative approach by analyzing previous literature, this study found that social media has a double impact; on the one hand it provides easy access to information and communication, but on the other hand it can lead to dependency that disrupts the educational process based on direct interaction and data-based decisions. Therefore, this study suggests the importance of digital literacy, mentoring in the use of social media, as well as the preparation of educational policies based on digital ethics to minimize the negative impact of social media in the educational environment.